2008
DOI: 10.1021/bm801109g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of Bcl-2-Targeted siRNA Using Cationic Polymer Nanoparticles: Downregulating mRNA Expression Level and Sensitizing Cancer Cells to Anticancer Drug

Abstract: In this study, cationic nanoparticles self-assembled from the amphiphilic copolymer poly(N-methyldietheneamine sebacate)-co-[(cholesteryl oxocarbonylamido ethyl) methyl bis(ethylene) ammonium bromide] sebacate) (P(MDS-co-CES) were synthesized and used to deliver Bcl-2 targeted siRNA into HepG2, HeLa and MDA-MB-231 cell lines, and downregulate Bcl-2 mRNA expression levels. Confocal microscopic studies show that the nanoparticles were able to complex with siRNA and deliver it inside the cells efficiently, but si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…18 Cationic NPs have been found to efficiently deliver small interfering RNA (siRNA) to silence target gene in cancer cells and also sensitize the cancer cells to the effect of paclitaxel (PTX) for improved anticancer activity. 19,20 Ligand-based targeting…”
Section: Surface Chargementioning
confidence: 99%
“…18 Cationic NPs have been found to efficiently deliver small interfering RNA (siRNA) to silence target gene in cancer cells and also sensitize the cancer cells to the effect of paclitaxel (PTX) for improved anticancer activity. 19,20 Ligand-based targeting…”
Section: Surface Chargementioning
confidence: 99%
“…Some studies have shown that Bcl-2 protein silencing with siRNA can sensitize cancer cells to anti-cancer drugs such as paclitaxel (Beh et al, 2008). Previous work showed that empty PEAL NPs had no therapeutic effects on SW620 colon cancer-bearing mice (Yin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…11 Previous research has shown that decreasing the expression level of Bcl-2 by the siRNA technique could efficiently trigger the apoptosis of cancer cells. 12,13 More importantly, the combination of chemotherapy and gene therapy such as Bcl-2 siRNA has been demonstrated to enhance the efficacy and improve the therapeutic outcome, [14][15][16][17] owing to the synergistic anticancer activity or enhanced sensitivity to chemotherapeutics.…”
Section: Introductionmentioning
confidence: 99%